Human Resource Management Strategy Analysis In Improving The Performance Of Employees With Disabilities at The UMKM Batik Ciprat Rumah Kinasih Kesamben District Blitar Regency - Amaria, Hanik; Guntarayana, Indria; Susilo, Eko Adi; Nasrullah, Aldo Muchammad (Universitas Islam Balitar, 2023)
In general, organizations or companies employ qualified and highly competent human resources to encourage business improvement. However, it is different for the Batik Ciprat Rumah Kinasih which actually recruits human resources with disabilities. The reason the owner founded Rumah Kinasih was because many people looked down on people with disabilities and people with mental disorders. They consider people with disabilities as people who do not have abilities and are considered a burden on the family. Viewed from the results of this research show that the human resource management strategies for improving the performance of employees with disabilities that Rumah Kinasih uses to improve their performance include recruitment strategies, training, work discipline and compensation. From the human resource management carried out, it is proven by good employee productivity which is shown, among other things, employees with disabilities arrive according to schedule, the batik products made are of good quality, the error rate is small, employees also have responsibility in carrying out tasks, and employees are active in Work.